Cultivation of infusoria as a starter live feed for marine finfish larvae - Mukai, Yukinori; Mohammad Noor, Normawaty; Affandi, Muhammad Muizzuddin (2017)
Infusoria are the microscopic single celled animalcules belonging to Class, Ciliata and Phylum, Protozoa. Seed production of marine finfish is still facing problem particularly on suitable live feed for early stage larvae. Currently, S- or SS-type rotifers, which have sizes from 100 to 200 μm, are used as live feed, however we are still searching smaller size live feed for starter diets. Early stage larvae of many marine finfish select feeds less than 100 μm. For example, Asian seabass selected 40-60 μm microcapsules when offered a range of 15-150 μm. In limited studies, infusoria has been identified to be optimum live feed, because their body sizes are less than 100 μm. Infusoria have been successfully used as live feed for limited number of marine finfish larvae with small size mouths. In nature, fish larval stomachs are reported to be filled with infusoria. In this study, we cultivated infusoria just using vegetable and fish meal. About 5000 cells /ml infusoria could be cultured. Larval rearing experiment was conducted using infusoria. Infusoria feeding larval group of Asian seabass showed better survival rate than rotifer feeding grouper.